Assessment of the food security level in the regions of the European North of Russia based on benchmarking methodology - O. G. Moronova (Publishing House of the State University of Management, 2020)
This paper justifies the need to use benchmarking tools when assessing food security in the regions of the European North of Russia. The authors reveal the essence and advantages of this approach, define the criteria that characterize the agrarian potential of the regions. On the basis of the author’s methodology, the study develops an algorithm for the benchmarking procedure and tests it on the subjects of the North-West Federal District. Based on the indicators of the formation and use of the agrarian potential and the applied ranking methodology, the paper reveals the similarity of five regions of the European North of Russia, substantiates the leading position of the agricultural sector of the Vologda region. As a result of the study, the authors make a conclusion that the level of food security in the region depends on the starting conditions of the region, relies on state and regional needs, takes into account the regulatory framework. This circumstance makes it necessary to constantly assess the level of food security in order to make appropriate decisions about the necessary management impacts.